AD, Volume 6, n° 2, 1981 - Full Issue - BUJRA, Abdalla S. (Africa Development, 1981)
CONTENTS Europe Undermined: The Lome Response. An Evaluation of the EEC- ACP Non Fuel Minerais Arrangement CECIL RAJANA .......................... 5 La Semi-Industrialisation Contemporaine P. JACQUEMOT .......................... 43 The Emerging Ideological Trends in the Non Aligned Movement: Some Reflections on the Havana Conference CLIFFORD EDOGUN ...................... 65 New Food Strategies and Social Transformation in East Africa YASH TANDON ............................. 86 South Africa, Jewish Palestine & Israel: The Growing Relationship 1919- 1974 J. A. KREINDLER ............................... 108 BOOK REVIEWS P. HEINECKE «Principles and Practice of Public Administration in Nigeria» ................. 143 «Administration for Development in Nigeria» .....................144 FOCUS ON RESEARCH & TRAINING INSTITUTES The Association of African Women for Research andDevelopment(AAWORD) ....... 147 Institute of Souther University of Lesotho ............ 149 BOOKS RECEIVED .................. 150